2010
DOI: 10.1590/s0006-87052010000100022
|View full text |Cite
|
Sign up to set email alerts
|

Adubação nitrogenada e incidência de brusone em arroz de sequeiro

Abstract: (IAC 201 e IAC 202). Foi empregada adubação de semeadura de 400 kg ha -1 de 0-14-08 de NPK acrescido de 1% de Zn e 0,5% de B, em todos os tratamentos. Intensa ocorrência de brusone, causada pelo fungo Pyricularia grisea, foi observada no experimento. Em condições de campo foram avaliadas a severidade de brusone nas panículas e a produtividade de grãos; em laboratório, a incidência de P. grisea nas panículas e nas sementes, a massa de mil grãos, o rendimento de grãos inteiros e quebrados, e a porcentagem de esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Regarding the optimal distribution of N fertilization, it was observed that the total application at topdressing was not the most effective, whereas the split application, which resulted in higher yields, was more effective. In addition, later fertilization at higher N concentrations can increase susceptibility to blast (Freitas et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the optimal distribution of N fertilization, it was observed that the total application at topdressing was not the most effective, whereas the split application, which resulted in higher yields, was more effective. In addition, later fertilization at higher N concentrations can increase susceptibility to blast (Freitas et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Normally, there is a deficiency of these two compounds in acid soils with low levels of organic matter, as stated by Tomm (2007). Nitrogen is the most requested nutrient and the one that most influences crop production whenever the remaining nutrients are found in satisfactory levels (Freitas et al, 2010;Melo et al, 2011). Rheinheimer et al (2007) observed that the areas with the largest canola crops in Brazil presented a deficiency of sulfur, mainly due to intense use of concentrated fertilizers without sulfur in their formulation and continuous extraction caused by harvesting.…”
mentioning
confidence: 99%